The secret life of sunflowers - Molnar, Marta, 1971- ([Marta Molnar], 2022)
While cleaning out her grandmother's New York brownstone, Emsley Wilson finds a diary that belonged to Johanna Bonger, Vincent van Gogh's sister-in-law, who inherited van Gogh's paintings. The paintings were worthless, Johanna was a 28 year old widow with a baby living in Paris, and she barely spoke the language. Yet she introduced van Gogh's legacy to the world. Emsley needs the inspiration. With her business failing, an unexpected love turning up in her life, and family secrets unraveling, can she find answers in the past? -- Provided by publisher.